Fuel Characteristics of Vine Prunings (Vitis vinifera L.) as a Potential Source for Energy Production - Ramadan A. Nasser; Mohamed Zidan Mohamed Salem; Hamad A. Al-Mefarrej; Mohamed A. Abdel-Aal; Said S. Soliman (BioResources, 2013)
Seven varieties of vine prunings (Vitis vinifera L.) grown under Riyadh conditions were considered as renewable sources for fuelwood. Significant effects (P<0.01) were found for total extractives, benzene-ethanol extractives, cellulose, hemicellulose, lignin, cold water solubility, and hot water solubility among the seven vine varieties. Highly significant positive correlations (P<0.01) were observed between the higher heating value (HHV) and benzene-ethanol extractives (r=0.74) and lignin content (r=0.94). Additionally, elemental composition (C, H, N, O, and S) exhibited a significant effect on HV (P<0.01) and ash content of the seven vine varieties. There were highly significant positive correlations (P<0.01) between the HV and C (r=0.96) and H (r=0.93). Ash content showed a highly significant effect (P<0.01) on HV with a negative coefficient (r=-0.93). The heating value of vine prunings ranged from 18.74 to 19.19 MJ/kg, i.e. higher than some well-known biomass fuels. The results suggested that the vine prunings could be suitable as a source for energy production in Saudi Arabia.